2020
DOI: 10.1111/1753-0407.13093
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the development of islet autoantibodies through integration of environmental, genetic, and metabolic markers

Abstract: Background: The Environmental Determinants of the Diabetes in the Young (TEDDY) study has prospectively followed, from birth, children at increased genetic risk of type 1 diabetes. TEDDY has collected heterogenous data longitudinally to gain insights into the environmental and biological mechanisms driving the progression to persistent islet autoantibodies. Methods: We developed a machine learning model to predict imminent transition to the development of persistent islet autoantibodies based on timevarying me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 50 publications
(100 reference statements)
0
45
0
Order By: Relevance
“…[46] Webb-Robertson et al, using the TEDDY cohort, reported that the top 42 features (of 221) gave an AUC of 0.65 for prediction of islet autoimmunity in the holdout validation set, appreciably lower than the AUC of 0.74 estimated with cross-validation of the training set. [45] As seen in our results, cross-validation is essential to avoid overfitting, even when using few features and a relatively large sample size (166 cases, 177 controls). Several factors influence the potential for overfitting and bias, but in general, the larger the number of predictors in relation to the number of subjects with outcome, and the more flexible modelling approach (allowing non-linearities and interactions), the larger the potential for overfitting.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…[46] Webb-Robertson et al, using the TEDDY cohort, reported that the top 42 features (of 221) gave an AUC of 0.65 for prediction of islet autoimmunity in the holdout validation set, appreciably lower than the AUC of 0.74 estimated with cross-validation of the training set. [45] As seen in our results, cross-validation is essential to avoid overfitting, even when using few features and a relatively large sample size (166 cases, 177 controls). Several factors influence the potential for overfitting and bias, but in general, the larger the number of predictors in relation to the number of subjects with outcome, and the more flexible modelling approach (allowing non-linearities and interactions), the larger the potential for overfitting.…”
Section: Discussionmentioning
confidence: 91%
“…[44] Webb-Robertson et al used a machine learning approach to predict islet autoimmunity using data from the TEDDY study (157 case-control pairs), reporting azelaic acid and adipic acid as important features. [45] Frohnert et al predicted seroconversion to islet autoimmunity in the DAISY study (22 cases and 25 controls) and reported 3-methyloxobutyrate (a precursor to valine for leucine synthesis) and pyroglutamatic acid (a derivative of glutamic acid) as features that were often selected by the algorithm used. [46] We did not find any strong associations between specific metabolites measured at birth and later type 1 diabetes.…”
Section: Metabolomics During Infancy and Early Childhood And Association With Islet Autoimmunity Or Type 1 Diabetes Have Been Investigatementioning
confidence: 99%
“…Frohnert et al, starting with 1552 features (and 22 cases), reported an AUC of 0.92 for prediction of islet autoimmunity in the DAISY study, without a holdout validation set ( 47 ). Webb-Robertson et al, using the TEDDY cohort, reported that the top 42 features (of 221) gave an AUC of 0.65 for prediction of islet autoimmunity in the holdout validation set, appreciably lower than the AUC of 0.74 estimated with cross-validation of the training set ( 46 ). As seen in our results, cross-validation is essential to avoid overfitting, even when using few features and a relatively large sample size (166 cases, 177 controls).…”
Section: Discussionmentioning
confidence: 93%
“…Stanfill et al used classification algorithms to determine the most predictive features of islet autoimmunity in the TEDDY study (504 samples) and reported adipic acid, creatinine, and leucine as influential metabolites ( 45 ). Webb-Robertson et al used a machine learning approach to predict islet autoimmunity using data from the TEDDY study (157 case-control pairs), reporting azelaic acid and adipic acid as important features ( 46 ). Frohnert et al predicted seroconversion to islet autoimmunity in the DAISY study (22 cases and 25 controls) and reported 3-methyl-oxobutyrate (a precursor to valine for leucine synthesis) and pyroglutamate acid (a derivative of glutamic acid) as features that were often selected by the algorithm used ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…More broadly, AI has been used in decision support systems for health care providers, for example by helping predict the onset of septic shock in intensive care patients [71]. AI is also showing promise for the prediction of early disease onset, for example by determining the probability of developing islet autoantibodies in type 1 DM [72], and for prognostication in those already diagnosed with disease, such as in the development of psychosis in patients with other high-risk psychiatric conditions [73].…”
Section: Data Analysis Approaches For Complex Multidimensional Data In Gdpmmentioning
confidence: 99%